Dyspnea—Think outside of the box, a case of subglottic stenosis - Wei Jia; Jack Porteus; Tass Malik (Clinical Case Reports, 2019)
Abstract Dyspnea is a common presentation in upper and lower airway obstructive causes. However, biphasic stridor and hoarseness should prompt evaluation of the upper airway. Nasendoscopy carried out by the otolaryngology team is a quick and an effective way of evaluating the upper airway.